Correlation of Family History of Diabetes Mellitus With Hyperglycaemia in Acute Stroke in Non Diabetic Patient - Patwary, Mohammad Shamsul Arefin; Ahasan, HAM Nazmul; Miah, Md Titu; Munmun, Farzana Rahman; Begum, Aysha; Shanchay, Shamsuddoha Sarker (Journal of Dhaka Medical College, 2023)
Background: Raised blood glucose is common in diabetic patients in early phase of stroke. It is also known that blood glucose level increases during acute stroke in non diabetic patients. Objective: Objective of this study was to assess the association between family history of diabetes and newly developed diabetes, impaired fasting glucose, impaired glucose tolerance during acute stroke in non diabetic patients. Methods: The purposive sampling method was applied to identify the patients by appropriate history taking about diabetes among the patients and their 1st degree relatives, documentary papers and laboratorial support evidenced by HbA1c level less than 6.5% (This means patient to be non diabetic). Data were collected from 100 patients. The data were collected by questionnaire, pre-tested earlier and data collection sheet illustrating the family history of diabetes mellitus and glycemic status during acute stroke among the nondiabetic patients. It was conducted from January, 2021 to July, 2021 in the Department of Medicine of Dhaka Medical College Hospital. Results: The study found that, mean age of the patents was 61.76±7.33 years. Family history of Diabetes Mellitus (first degree relative) was found among 48% patients.52% patients did not give family history of Diabetes Mellitus. During analysis of the lab investigations among the participants, mean HbA1c level was found 5.69± 0.65 mmol/L which was found normal among the entire patient group. Patients Fasting Blood Sugar (FBS) was tested and mean FBS level was 5.94±0.86.Among the respondents 48% gave family history(1st degree relative) of Diabetes of which 8.3% revealed normal glycemic status , 66.7% showed IGT and 25.0% were diabetic. On the other hand 52% respondents had no family history of Diabetes, among them 50% showed no glycemic abnormality, 42.3% showed IGT and only 7.7% were diabetic. Conclusion: In a nutshell, the study finds that, in patients with no history of diabetes who have acute stroke, may develop moderately elevated glucose levels and it is significantly higher in those who have family history of diabetes mellitus. J Dhaka Med Coll. 2021; 29(1): 38-42